Biomaterials Loaded with Growth Factors/Cytokines and Stem Cells for Cardiac Tissue Regeneration - Saltanat Smagul (International Journal of Molecular Sciences, 2020)
Myocardial infarction causes cardiac tissue damage and the release of damage-associated molecular patterns leads to activation of the immune system, production of inflammatory mediators, and migration of various cells to the site of infarction. This complex response further aggravates tissue damage by generating oxidative stress, but it eventually heals the infarction site with the formation of fibrotic tissue and left ventricle remodeling. However, the limited self-renewal capability of cardiomyocytes cannot support sufficient cardiac tissue regeneration after extensive myocardial injury, thus, leading to an irreversible decline in heart function. Approaches to improve cardiac tissue regeneration include transplantation of stem cells and delivery of inflammation modulatory and wound healing factors. Nevertheless, the harsh environment at the site of infarction, which consists of, but is not limited to, oxidative stress, hypoxia, and deficiency of nutrients, is detrimental to stem cell survival and the bioactivity of the delivered factors. The use of biomaterials represents a unique and innovative approach for protecting the loaded factors from degradation, decreasing side effects by reducing the used dosage, and increasing the retention and survival rate of the loaded cells. Biomaterials with loaded stem cells and immunomodulating and tissue-regenerating factors can be used to ameliorate inflammation, improve angiogenesis, reduce fibrosis, and generate functional cardiac tissue. In this review, we discuss recent findings in the utilization of biomaterials to enhance cytokine/growth factor and stem cell therapy for cardiac tissue regeneration in small animals with myocardial infarction.